Sources of resistance in Musa to Xanthomonas campestris pv. musacearum, the causal agent of banana xanthomonas wilt - Nakato, G.V.; Christelova, P.; Were, E.; Nyine, M.; Coutinho, Teresa A.; Doležel, Jaroslav; Uwimana, Brigitte; Swennen, Rony L.; Mahuku, George S. (Wiley, 2019)
It is claimed that, with the exception of Musa balbisiana, all banana varieties are susceptible to bacterial wilt caused by Xanthomonas campestris pv. musacearum (Xcm). Despite being resistant to Xcm infection, M. balbisiana is not preferred for breeding because it belongs to the BB genome subgroup, while most edible bananas are of the A genome. To identify potential sources of resistance to Xcm, 72 banana accessions representing the Musa genetic diversity were evaluated in an outdoor confined potted trial. The midribs of the youngest leaf of 3-month-old banana plants were inoculated with 108 CFU mL 1 of Xcm isolate USY13P, and symptom development assessed weekly for 4 months. Results confirmed that M. balbisiana genotypes are indeed resistant to Xcm. Varieties within the Musa acuminata subsp. zebrina (AA) set were further identified as potentially useful sources of Xcm resistance. These findings reveal the potential to develop banana and plantain varieties with tolerance to Xcm.